PWE-395 Patient and clinical risk factors for incisional hernia following reversal of loop ileostomy. (22nd June 2015) - Brook, A; Mansfield, S; Daniels, I; Smart, N
Abstract : Introduction: Loop ileostomy reversal is commonly performed, with reported rates of ileostomy-site incisional hernia between 0–48%. Risk factors of patients developing post-reversal hernias are poorly understood. Method: We performed a retrospective study of patients undergoing loop ileostomy reversal during five years 1 st January 2009 to 31 st December 2013. The primary outcome was ileostomy-site incisional hernia, detected clinically and, as a gold standard, by computed tomography scans or ultrasonography. Data were extracted on preoperative factors (age, BMI, smoking, preoperative marking, surgical indication), intraoperative decisions (rectus sheath suture, skin suture, closure method) and postoperative events (complication (<30days), followup duration). Data were analysed with SPSS version 21. Statistics are median (IQR) and correlations Spearman's rho. P < 0.05 was considered statistically significant. Results: In total, 180 patients underwent loop ileostomy closure. Baseline demographics were as follows: age (66 years (26), BMI 25kg/m 2 (5.8) and 28 patients (16%) were smokers. Indication for ileostomy was rectal cancer (n = 98; 54.4%), followed by inflammatory bowel disease (n = 40; 22.2%), diverticulosis (n = 19; 10.6%), inflammatory fistulae (n = 4; 2.2%), and assorted indications (n = 16; 8.9%). Overall incidence of ileostomy-site incisional hernia was 19%, occurring at a median of 8 months (IQR 15). Overall duration of postoperative follow up was 20 months (IQR 28). Clinical detection of hernia compared to CT/US was 88% and all clinically-evident cases were identified radiologically. Four cases not evident clinically were detected by radiology alone. 64% of hernias required reoperation. Surgical indication was a significant hernia determinant (χ 2 p < 0.001) with a higher incidence in cancer patients. 66% of patients were marked preoperatively. Post-closure complications occurred in 22% of patients and predicted higher hernia risk (χ 2 p < 0.001). BMI was a major risk factor for ileostomy-site hernia (Mann Whitney P = 0.04; R=.236; P = 0.002). Patients with higher blood pressure at closure had a higher incidence of hernias (Mann Whitney P = 0.009). Age and smoking were not significant factors (R = -0.018 and 0.005 respectively; P > 0.05 for both). Choice of suture material for rectus sheath (PDS vs. Prolene) or skin (Monocryl vs. Maxon) did not predict hernia (R=-0.113 and -0.041 respectively; both P > 0.05). Healing by secondary intention was not associated with higher hernia incidence (R = 0.004; P > 0.05). Conclusion: Ileostomy-site hernia occurs in approximately one fifth of patients. Patient factors such as BMI and preoperative co-morbidity remain the greatest predictors of hernia. Variability in operative practice such as choice of suture material and the method of skin closure does not impact hernia risk. Disclosure of interest: None Declared.